2016
DOI: 10.1021/acsami.6b05677
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Chemo–Photothermal Therapy of Breast Cancer by Mesenchymal Stem Cell-Encapsulated Yolk–Shell GNR@HPMO-PTX Nanospheres

Abstract: Mesenchymal stem cells (MSCs) have attracted increasing attention as vehicles for cancer treatment. Herein, MSC-based synergistic oncotherapy strategy is presented for the first time. To achieve this goal, yolk-shell structured gold nanorod embedded hollow periodic mesoporous organosilica nanospheres (GNR@HPMOs) with high paclitaxel (PTX) loading capability and excellent photothermal transfer ability upon near-infrared (NIR) light irradiation are first prepared. Cytotoxicity and migration assays show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 54 publications
0
59
0
1
Order By: Relevance
“…B) TEM micrographs displaying the variety of morphologies and structures of MONs and PMO NPs for biomedical applications. Reproduced with permissions from American Chemical Society, Royal Society of Chemistry, Elsevier, Springer, and Wiley …”
Section: Synthesis and Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…B) TEM micrographs displaying the variety of morphologies and structures of MONs and PMO NPs for biomedical applications. Reproduced with permissions from American Chemical Society, Royal Society of Chemistry, Elsevier, Springer, and Wiley …”
Section: Synthesis and Propertiesmentioning
confidence: 99%
“…Magnetic core–shell NPs can be applied for hyperthermia and temperature‐triggered cargo release ( B7 , C7 ). Gold core–shell NPs are usually applied for photodynamic therapy and imaging thanks to their plasmonic properties ( F3 , F7 , A8 , B8 , C8 , D8 ). Prussian blue core–shell NPs are widely studied for magnetic resonance and photoacoustic imaging, as well as photothermal therapy ( E3 ).…”
Section: Synthesis and Propertiesmentioning
confidence: 99%
“…In vitro PDT efficacy showed that the viability of human lung cancer cells significantly decreased to 10% after incubating with 0.05 mg mL −1 of the UCNP@HPMOs and exposing to a 980 nm irradiation (0.5 W cm −2 , 10 min) (Figure b). Wu et al prepared gold nanorod‐embedded hollow PMO nanospheres to load PTX (GNR@HPMOs‐PTX) for synergistic photothermal and chemical therapy . The resultant GNR@HPMOs‐PTX showed excellent photothermal transfer ability, which raised the temperature as high as 45.6 and 92.4 °C upon a laser irradiation for 5 min at the concentrations of 100 and 1000 µg mL −1 , respectively.…”
Section: Applicationsmentioning
confidence: 99%
“…c) Photoacoustic imaging of breast cancer in subcutaneous dorsa of the mouse before and after 24 h intratumoral injection of gold nanorod and paclitaxel (PTX) coloaded hollow PMOs (denoted as GNR@HPMOs‐PTX) and GNR@HPMOs‐PTX loaded mesenchymal stem cells (MSCs), and d) representative photos of MCF‐7 tumor‐bearing mice from MSCs alone, GNR@HPMOs, GNR@HPMOs‐PTX, GNR@HPMOs@MSCs, and GNR@HPMOs‐PTX@MSCs at 14 d after the laser irradiation, respectively. c,d) Reproduced with permission . Copyright 2016, American Chemical Society.…”
Section: Applicationsmentioning
confidence: 99%
“…Hypoxic‐treated neural stem cells showed the overexpression of CXCR4 and could enhance the tumor migration ability 23. There were numerous studies utilized the homing ability of stem cells for tumor targeting 24, 25, 26, 27, 28. In addition, it has been reported that iron oxide nanoparticles with the released iron ions could increase the CXCR4 expression on the mesenchymal stem cell (MSC) surface and promote the migration ability 29.…”
Section: Introductionmentioning
confidence: 99%